THE IMPLEMENTATION OF PONTIANAK CITY'S ONE DATA POLICY FOR REGIONAL DEVELOPMENT PLANNING - Handayani, Tri Murti (JPASDEV : Journal of Public Administration and Sociology of Development, 2024)
The purpose of writing this thesis is to find out, explain, and analyze the process of implementing the Pontianak City One Data Policy for Regional Development Planning at the Pontianak City Communication and Information Service. This thesis uses a descriptive research type and qualitative approach. The results obtained are: implementation of Pontianak City's One Data Policy for Regional Development Planning, although it requires improvements in the stages of organization, interpretation, and application, generally running on track according to the Pontianak City One Data Action Plan for 2022. New theoretical findings in the policy implementation process are needed: intense and simultaneous coordination and communication between implementers; empowerment of human resources in the smallest implementing units to overcome human resource shortages; and the commitment of all implementers to the action plan that has been determined. Recommendations formulated: direct coordination with BAPPENAS to clarify the integration of the Pontianak City One Data portal; coordinate with the geospatial data supervisor to accelerate the management of geospatial data; conduct outreach to the Pontianak City One Data policy and portal to the public; compiling and implementing the SOP for the Implementation of One Data for Pontianak City; improve human resource competency; and increasing the amount of indicator data, updating data regularly, and displaying time series data.